The making of economics - Canterbery, E.Ray (World Scientific Publishing Co. Pte.Ltd., 2003)
Includes chapters on the casino economy (a term the author invented to describe an economy driven by making money with money rather than focusing on real production, now overtaken by reality), Joseph Schumpeter, globalization, and general equilibrium. In this book, economics is displayed as a developing discipline, a discipline still evolving